Human Error in Traffic Accidents: Differences between Car Driver and Motorcyclist Experiences - Santoso, Guritnaningsih P.; Maulina, Dewi (Psychological Research on Urban Society, 2019)
Traffic accidents are one of the main causes of death in Indonesia, with human error being found to play a major role. The aim of this study is to analyze the human error factors that contribute to car and motorcycle traffic accidents. The data were collected from interviews with five car drivers and five motorcyclists from five Indonesian cities (Aceh, Pekanbaru, Semarang, Pontianak, and Gorontalo). The research found that there were no recognition error and decision error differences between car drivers and motorcyclists as both made recognition errors such as misestimations of distance and speed, and both made decision errors such as not avoiding a situation immediately, and performance errors such as stepping on the gas pedal by mistake. However, they were differences in other errors. For example, drivers tended to become sleepy, whereas motorcyclists felt tired, under time pressure, and did not have proper licenses. The results of this study could be used to make drivers/riders more aware of the cognitive aspects that contribute to road safety.